Anaerobic performance when rehydrating with water or commercially available sports drinks during prolonged exercise in the heat - Del Coso, J.; Estevez, E.; Baquero, R. A.; Mora-Rodriguez, R. (Applied Physiology, Nutrition, and Metabolism, 2008)
The effects that rehydrating drinks ingested during exercise may have on anaerobic exercise performance are unclear. This study aimed to determine which of four commercial rehydrating drinks better maintains leg power and force during prolonged cycling in the heat. Seven endurance-trained and heat-acclimatized cyclists pedaled for 120 min at 63% maximum oxygen consumption in a hot, dry environment (36 °C; 29% humidity, 1.9 m/s airflow). In five randomized trials, during exercise, subjects drank 2.4 ± 0.1 L of (i) mineral water (WAT; San Benedetto®), (ii) 6% carbohydrate-electrolyte solution (Gatorade® lemon), (iii) 8% carbohydrate-electrolyte solution (Powerade® Citrus Charge), (iv) 8% carbohydrate-electrolyte solution with lower sodium concentration than other sports drinks (Aquarius® orange), or (v) did not ingest any fluid (DEH). Fluid balance, rectal temperature (Trec), maximal cycling power (Pmax), and leg maximal voluntary isometric contraction (MVC) were measured. During DEH, subjects lost 3.7 ± 0.2% of initial body mass, whereas subjects lost only 0.8% ± 0.1% in the other trials (p < 0.05). Final Trec was higher in DEH than in the rest of the trials (39.4 ± 0.1 °C vs. 38.7 ± 0.1 °C; p < 0.05). Pmax was similar among all trials. Gatorade® and Powerade® preserved MVC better than DEH (-3.1% ± 2% and -3.8% ± 2% vs. -11% ± 2%, p < 0.05), respectively, whereas WAT and Aquarius® did not (-6% ± 2%). Compared with DEH, rehydration with commercially available sports drinks during prolonged exercise in the heat preserves leg force, whereas rehydrating with water does not. However, low sodium concentration in a sports drink seems to preclude its ergogenic effects on force.